2017
DOI: 10.1177/1010428317697575
|View full text |Cite
|
Sign up to set email alerts
|

MiR-138: A promising therapeutic target for cancer

Abstract: MicroRNAs are small noncoding RNAs which regulate gene expressions at post-transcriptional level by binding to the 3'-untranslated region of target messenger RNAs. Growing evidences highlight their pivotal roles in various biological processes of human cancers. Among them, miR-138, generating from two primary transcripts, pri-miR-138-1 and pri-miR-138-2, expresses aberrantly in different cancers and is extensively studied in cancer network. Importantly, studies have shown that miR-138 acts as a tumor suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 90 publications
4
55
0
Order By: Relevance
“…It has been reported that important signaling pathways in CRC, such as the Wnt/β-catenin, RAS, p53, TGF-β, NF-kB pathways, are regulated by miRNAs [2123]. A number of studies have demonstrated that miR-138 regulates various molecular pathways and is associated with initiation and progression of cancer, and thus is considered as a potential tumor suppressor [24]. As reported by Jiang et al[25], ectopic transfection of miR-138 contributed to the reduced migration and invasion in oral tongue squamous cell carcinoma by targeting RhoC and ROCK2, which are involved in the remodeling of cellular cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that important signaling pathways in CRC, such as the Wnt/β-catenin, RAS, p53, TGF-β, NF-kB pathways, are regulated by miRNAs [2123]. A number of studies have demonstrated that miR-138 regulates various molecular pathways and is associated with initiation and progression of cancer, and thus is considered as a potential tumor suppressor [24]. As reported by Jiang et al[25], ectopic transfection of miR-138 contributed to the reduced migration and invasion in oral tongue squamous cell carcinoma by targeting RhoC and ROCK2, which are involved in the remodeling of cellular cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that miR-138 was up-regulated by ANGPTL1, but the mechanism of its biogenesis remains unexplored. As reported, epigenetic and transcription factors, as well as many other molecules, are correlated with miR-138 expression [24]. For example, miR-138 expression can be decreased by methylation of its DNA [27] and up-regulated by a histone deacetylase inhibitor [28] and overexpression of P 19 H-Ras [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have confirmed that miRNAs play essential roles in the diagnosis, development, prognosis, and treatment of a variety of tumors. miRs will become potential therapeutic targets, anticancer agents, and biomarkers for the treatment of cancer and bring novel guidance in molecular targeting treatment of cancers in the future . Approximately about 85% of lung diseases are associated with non‐small cell lung cancer (NSCLC), it is one of the most leading causes of cancer mortality and the most prevalent cancers.…”
Section: Introductionmentioning
confidence: 99%
“…miRs will become potential therapeutic targets, anticancer agents, and biomarkers for the treatment of cancer and bring novel guidance in molecular targeting treatment of cancers in the future. [80][81][82][83] Approximately about 85% of lung diseases are associated with non-small cell lung cancer (NSCLC), it is one of the most leading causes of cancer mortality and the most prevalent cancers. Its development and occurrence are closely associated with tumor angiogenesis.…”
mentioning
confidence: 99%